Estimates of the initial impact of the COVID-19 epidemic on overall mortality: evidence from Italy. Issue 2 (29th June 2020) - Conti, Sara; Ferrara, Pietro; Fornari, Carla; Harari, Sergio; Madotto, Fabiana; Silenzi, Andrea; Zucchi, Alberto; Manzoli, Lamberto; Mantovani, Lorenzo G.
From February 2020, when the first case of coronavirus disease 19 (COVID-19) was detected, Italy has rapidly become one of the countries most affected by the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), accounting for 135 586 recorded cases as of 7 April 2020 [1]. Surveillance data from the National Institute of Health indicate that COVID-19 has caused more than 15 000 lethal pneumonia cases, particularly in some of the northern regions. Positive cases had a median age of 62 years, while patients who died of COVID-19 had a median age of 80 years [2]. This study provides evidence of the enormous death toll attributable to COVID-19 https://bit.ly/2X4C6a8